Advancing values-based approaches to climate change adaptation: A case study from Australia. Issue 76 (October 2017) - Ramm, Timothy David; Graham, Sonia; White, Christopher John; Watson, Christopher Stephen
Highlights: Diverse lived values—recreation, scenery and safety—are at risk of sea-level rise. Only a subset of natural landscape units at risk are highly valued by residents. Distinct groups of residents have unique sets of lived and landscape values. Equitable adaptation policies require accommodating diverse lifestyles and values. A combination of lived and landscape approaches can better inform adaptation policy. Abstract: Coastal flooding affects physical and social place attachments. Values-based approaches to climate change adaptation examine how risks to place attachments are distributed within and among communities, with a view to informing equitable adaptation policies. In this nascent body of research, divergent theoretical frameworks and empirical approaches to measuring social values are evolving. While some studies explore the things people value about their everyday lives generally—the lived values approach, others locate specific social and cultural values in geographic space—the landscape values mapping approach. This study aims to compare the explanatory value of these two approaches for understanding the social risks of sea-level rise, and appraise whether either or both approaches are likely to meet local adaptation planning needs. It does this by examining the potential social impacts of sea-level rise in Kingston Beach, Australia, informed by a mail-out survey of the community. The lived values approach identified that the natural environment, scenery, relaxed lifestyle and safety are highly important to local residents, while the landscape values mapping approach revealed that Kingston Main Beach is the most highly valued of eight coastal landscape units. Incorporating the landscape values mapping into the lived values cluster analysis revealed that while Kingston Main Beach is highly important for its recreational value to some members of the community, for others manmade features such as community halls or sports ovals may be of higher importance because they facilitate social interactions. There is potential to further integrate these two approaches to better inform adaptation policy about how lived and landscape values are distributed among communities, where they are located in space and whether they change over time. A deeper understanding of such assigned values can lead to improved engagement with coastal residents to inform adaptation policy now and into the future.